Alkaline comet assay in DNA damage assessment in frozen whole blood samples without cryopreservation: results of the hCOMET Group - Milić, M. (2022)
As a worldwide-used, simple, sensitive, and inexpensive technique, alkaline comet assay can give reliable results in the assessment of strand breaks (SBs) and alkali-labile sites. In human biomonitoring, fresh blood samples (whole blood, isolated mononuclear cells, and their cell fractions) are usually used, but the assay can be used also on cryo-preserved samples of freshly isolated peripheral blood mononuclear cells (PBMC). When processing a large number of whole blood samples into isolated PBMC ready for freezing, this process can be time-consuming, and cryo-preservatives (dimethyl sulfoxide/glycerol) can harm cells and increase DNA damage levels after thawing. The need has emerged to develop a relatively simple protocol that can be applied immediately even to small volumes of stored frozen whole blood without the cryopreservative. The presentation will show the findings from our hCOMET group demonstrating new protocols using smaller whole blood volumes (250 μl-1 ml) for freezing, fast thawing with normal comet assay conditions (5–10 μl sample, 0.5−0.6% agarose layer, counting nucleoids only in the slides central part avoiding edges) that demonstrated reproducible results with freezing conditions of up to three months but also, even more, one or few years. Oxidative measurements after 11 months of blood storage at −80° C demonstrated also promising and comparable results. These findings could be useful in retrospective studies, in future prospective studies, and to re-analyze putative outliers in the dataset.